Theosis and forgiveness in the Gospel of Matthew - Kim, Kangil (Lexington Books/Fortress Academic, 2024)
"In this book, Kangil Kim reads the Matthean teaching of forgiveness through the framework of theosis. Kim argues that theosis provides a theological lens that brings into sharper focus the meaning of forgiveness, especially with respect to the dynamics of heaven and earth and of God and the human in Matthew's Gospel"--